2014
DOI: 10.3892/ijo.2014.2427
|View full text |Cite
|
Sign up to set email alerts
|

Podocalyxin-like 1 is associated with tumor aggressiveness and metastatic gene expression in human oral squamous cell carcinoma

Abstract: Metastasis-mediated death remains a major challenge in cancer treatment due to the lack of identifiable biomarkers for early diagnosis. Identifying tumor-specific biomarkers is critical for the development of diagnostic and therapeutic tools. In the present study, we found that podocalyxin-like 1 (PODXL), a cell surface glycoprotein, was overexpressed in cancer tissues and was upregulated in lymph node metastatic tumor cells. The expression of PODXL was associated with the migratory ability of human oral squam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 54 publications
2
34
0
Order By: Relevance
“…PODXL was previously reported to enhance tumor aggressiveness in breast cancer, prostate cancer, oral squamous cell carcinoma and astrocytoma (56)(57)(58)(59). hsu et al reported PODXL-ebP50-ezrin molecular complex enhances the metastatic potential of renal cancer through recruiting RAC1 guanine nucleotide exchange factor, ARhgeF7 (60).…”
Section: Discussionmentioning
confidence: 99%
“…PODXL was previously reported to enhance tumor aggressiveness in breast cancer, prostate cancer, oral squamous cell carcinoma and astrocytoma (56)(57)(58)(59). hsu et al reported PODXL-ebP50-ezrin molecular complex enhances the metastatic potential of renal cancer through recruiting RAC1 guanine nucleotide exchange factor, ARhgeF7 (60).…”
Section: Discussionmentioning
confidence: 99%
“…74 In studies conducted with oral squamous cell carcinoma (OSCC) cells, podocalyxin-like 1 protein, a sialomucin, is needed for OSCC migratory, invasive, and proliferative properties. 75 Podocalyxin-like 1 protein promotes invadopodia formation by regulating cortactin phosphorylation and Ras-related C3 botulinum toxin substrate 1 (Rac1)/cell division cycle 42 (CDC42) activity. 76 In squamous cell carcinoma cells, podoplanin, a type 1 transmembrane glycoprotein, localizes to invadopodia-associated adhesion rings and serves an important role in the stabilization of invadopodia.…”
Section: Commentmentioning
confidence: 99%
“…The overexpression of PCLP1 has been associated with a more aggressive phenotype and poor prognosis in numerous types of cancer, including breast, colorectal, prostate, bladder, ovarian cancer, renal carcinoma, and oral squamous cell carcinoma, which suggests an important role of this protein in cancer progression and metastasis, although the underlying mechanisms are poorly understood (6269). PCLP1 is also overexpressed in blasts of acute leukemia, testicular tumor, hepatic carcinoma, astrocytic tumor, and small cell lung carcinoma (7074).…”
Section: Pclp1 a Selectin Ligand Involved In Platelet–tumor Interactionmentioning
confidence: 99%